Beyond privacy calculus: public acceptance of non-invasive therapeutic brain-computer interfaces in China - Haoyu Wang; Mei Yin (Frontiers in Public Health, 2026)
Background and objective Non-invasive brain–computer interfaces (BCIs) are rapidly transitioning from laboratory settings to clinical rehabilitation and mental health applications. However, unlike ordinary consumer technologies, therapeutic BCIs are adopted under health imperatives rather than discretionary choice. In such contexts, the “privacy calculus” logic underlying the Value-based Adoption Model (VAM), which assumes users rationally weigh benefits against sacrifices, may not adequately capture adoption decisions. This study aimed to explore the public’s acceptance of non-invasive therapeutic BCIs in China, identify influencing factors, and examine the moderating roles of age, monthly income, and disease status. Methods Using a cross-sectional survey design, 337 valid questionnaires were collected from Chinese adults via snowball sampling on the Wenjuanxing online platform. A structural equation model (SEM) incorporating perceived benefit, perceived sacrifice, perceived value, and a second-order latent variable “external drivers” was constructed and tested. Hierarchical regression analysis examined moderation effects. Results The mean usage intention score was 3.93 (SD = 0.63). Perceived benefit strongly and positively predicted perceived value ( β = 0.951, p < 0.001), while perceived value ( β = 0.749, p < 0.001) and external drivers ( β = 0.241, p = 0.027) positively predicted usage intention. The negative effect of perceived sacrifice on perceived value was non-significant ( β = −0.091, p = 0.061); a post-hoc power analysis confirmed the study was adequately powered (power > 0.99 for a medium effect), suggesting this effect is negligible. Age positively moderated the “perceived sacrifice → perceived value” path ( β = 0.118, p < 0.01), with older respondents showing greater tolerance for technological costs. Conclusion In the context of non-invasive therapeutic BCIs, the negative effect of perceived sacrifice on perceived value was not supported, suggesting that the classic privacy calculus logic may be attenuated when health imperatives are salient. We propose “cost desensitization” as a tentative mechanism warranting further mixed-methods validation research. These findings inform clinical expectation management and ethical governance of emerging neurotechnologies.